Pengaruh Disiplin Kerja Dan Kompetensi Profesional Terhadap Kinerja Guru Di SDIT Atikah Musaddad - Puja Fachri Hazami; Barin Barlian; Ai Kusmiati Asyiah (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims to identify and analyze the influence of work discipline and professional competence on teacher performance at SDIT Atikah Musaddad. The population in this study were teachers with a survey approach and data analysis techniques using multiple linear regression. Based on the data that has fulfilled the validity test, reliability test, and classic assumption test it is processed to produce the regression equation as follows Y = 10.114 + 0.272X1 + 0.457X2 + e. The test results show that work discipline and professional competence simultaneously have a significant effect on teacher performance at SDIT Atikah Musaddad. Partially Work Discipline and Professional Competence have a significant effect on Teacher performance at SDIT Atikah Musaddad.